Outbreak of Human Parainfluenza Virus Type 1 in a Kindergarten from China, 2018 - Li, Hong-Jun; Du, Juan; Yang, Yan-Na; Cui, Yan; Xi, Lu; Wang, Shuai; Liu, Ya-Qiong; Zhang, Guo-Feng; Cui, Fuqiang; Lu, Qing-Bin (Journal of Pediatric Infectious Diseases, 2020)
Objective We reported an outbreak of human parainfluenza virus type 1 (HPIV1) in a kindergarten and explored the genetic characteristics of HPIV1 hemagglutinin-neuraminidase (HN) and fusion (F) genes to provide more evidence about HPIV1 outbreaks.Methods Suspected cases were the children with an influenza-like illness during June 20 to 26, 2018. Nasopharyngeal swabs were collected and screened to determine the presence of respiratory pathogens by real-time fluorescent quantitative polymerase chain reaction. The HN and F gene sequences of HPIV-positive samples were further amplified and sequenced to confirm the HPIV genotype and identify genetic characteristics. A phylogenetic tree, based on the HN and F genes, was reconstructed by maximum likelihood method.Results Fourteen children in the outbreak were diagnosed as upper respiratory tract infection. The most common symptom was cough (10/14), followed by rhinorrhea (5/14), sore throat (4/14), headache (1/14), and abdominal pain (1/14). Eight patients were positive for HPIV1 and negative for other pathogens. Phylogenetic tree demonstrated that the eight strains from the year 2018 in our study located in the clade 2.3. Two specific substitutions (N333S and I509M) in the amino acids of the F protein and two substitutions (V19A and L436I) in the HN protein were different from other strains in the clade 2.Conclusion HPIV1 was attributed to the outbreak, which may be related to the genetic variations of HPIV1.
Keywords: outbreak; parainfluenza virus; children